1997
DOI: 10.1039/a604534k
|View full text |Cite
|
Sign up to set email alerts
|

Generation of homochiral aziridinium ion intermediates derived from 2,3-epoxy amines: regiospecific nucleophilic trapping with nitrogen nucleophiles. Application in the synthesis of novel morpholinosphingolipid analogues with potential glucosylceramide synthase inhibitory activity

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 78 publications
0
10
0
1
Order By: Relevance
“…Further insight into the mechanism and driving force for the counterion exchange was gained by evaluating the solubilities of the reacting partners in the MTBE phase. As can be seen from Table , these studies revealed that, while β-chloroamine 12 was soluble in MTBE to 115 mg/mL, aziridinium mesylate 10a was only soluble to 5 mg/mL and Et 3 N·HCl was soluble to less than 0.1 mg/mL. These data point to a biphasic process wherein counterion exchange occurs upon precipitation of 10a and β-chloroamine 12 is re-extracted into the MTBE phase (Scheme ).…”
Section: Resultsmentioning
confidence: 79%
“…Further insight into the mechanism and driving force for the counterion exchange was gained by evaluating the solubilities of the reacting partners in the MTBE phase. As can be seen from Table , these studies revealed that, while β-chloroamine 12 was soluble in MTBE to 115 mg/mL, aziridinium mesylate 10a was only soluble to 5 mg/mL and Et 3 N·HCl was soluble to less than 0.1 mg/mL. These data point to a biphasic process wherein counterion exchange occurs upon precipitation of 10a and β-chloroamine 12 is re-extracted into the MTBE phase (Scheme ).…”
Section: Resultsmentioning
confidence: 79%
“…The direction of the equilibrium of the aza-Payne rearrangement of epoxy amines has been investigated by many research groups. [9][10][11][12][13][14][15][16][17]19 It is well established by Rayner [9][10][11] that quantitative generation of quaternary aziridinium salt 98 could be accomplished by exposure of 2,3-epoxy N,N-diallylamine 97 to trimethysilyl triflate (Scheme 16); a process that is essentially irreversible. However, desilylation of the aziridinium salt 98 by treatment with potassium carbonate in methanol regenerates the original 2,3-epoxy diallylamine 97 and it would appear that, at least in this present case, desilylation and subsequent aziridinium ion ring-opening to yield original 2,3-epoxy amine 97 is a more favourable process.…”
Section: Aza-payne Rearrangement Reaction Of 23-epoxy Aminesmentioning
confidence: 99%
“…8 Recently, by using Lewis acids such as TMSOTf, N,Ndibenzylated or N,N-diallylated 2,3-epoxy amines, compounds of type 6 have been reported by Rayner and co-workers to rearrange to the aziridinium salts 7 which open at the more reactive C-1 position with various nucleophiles to yield the rearrangement-opening products 8. [9][10][11] For example, the 2,3-epoxy-N,N-diallylamine derivative 6 (R 1 = Pr n , R 2 = H) was treated with TMSOTf to yield the aziridinium salt 7 in quantitative yield. Removal of the trimethylsilyl group of 7 with potassium carbonate in methanol and subsequent intramolecular rearrangement regenerated the original epoxy amine starting material 6 in a high yield.…”
Section: Introductionmentioning
confidence: 99%
“…The cleavage of C–N allylic bonds in N ‐allyl‐ and N , N ′‐diallylamines can be performed in good yields by refluxing the substrate in ethanol in the presence of one equivalent of methanesulfonic acid and a catalytic amount of Pd/C 58,59. The mechanism proceeds as with allyl ethers by migration of the double bond 60.…”
Section: Base‐catalyzed and Transition‐metal‐catalyzed 13‐hydrogementioning
confidence: 99%